PENGARUH FINANCIAL DISTRESS DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Siti Alifah Fauziyah; Rian Sumarta (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The objective of this research is to obtain empirical evidence about the effect financial distress, managerial ownership, audit committee, size board of director, size of the independent board of commissioners, institutional ownership, and profitability on tax avoidance. The population in this research is manufacturing companies listed in Indonesia Stock Exchange from the year of 2019-2021. Samples were obtained through a purposive sampling method in which 234 data were taken as the sample. This research uses multiple regression methods to test the hypotheses. The result of this research indicated that financial distress, institutional ownership and profitability have negative effects on tax avoidance. Meanwhile the result of this research then shows that managerial ownership, audit committee, size board of director and size of the independent board of commissioners do not have effect on tax avoidance.